Behaviour of subballast reinforced with used tyre and potential application in rail tracks. (September 2017) - Indraratna, Buddhima; Sun, Qideng; Grant, Jim
Abstract: Rubber tyres have a three dimensional cylindrical structure, and as such could be used to stabilise foundations by increasing the bearing capacity and reducing settlement for transport infrastructure. It is therefore expected that in railroad engineering, a capping layer reinforced with rubber tyres could help to reduce the thickness of the granular layer (i.e. ballast), improve the track bearing capacity, and reduce the frequency of maintenance. However, there is a notable gap between the conceptual theories and real-life applications pertaining to the mechanisms of rubber tyre-reinforced foundations. In pavement engineering, the bearing capacity is closely linked to plate load tests. In this study, plate load tests were carried out on a single tyre filled with subballast material and subjected to a vertical load. This testing process was then modelled using the Finite Element software ABAQUS to study and quantify the interaction between the tyre and the granular medium. The experimental and numerical results reveal that the rubber tyre can significantly increase the modulus and ultimate bearing capacity of the granular layer. The numerical process was further extended to a finite element track model to demonstrate the expected response of a ballasted railway track with and without tyre reinforcement.